Evaluation and comparison of serum and salivary interleukin 9 levels among individuals with gingivitis and periodontitis and healthy controls: A cross-sectional study - P. Abhigna; Jammula Surya Prasanna; Rekha Rani Koduganti (Wolters Kluwer Medknow Publications, 2024)
Context: Although interleukin (IL)-9 has been understudied, some pleiotropic effects have been documented on lymphocytes and mast cells. It is a T-cell-derived cytokine. Aims: The aim of this study was to appraise the association of IL-9 in the serum and saliva of individuals with gingivitis, periodontitis, and healthy controls. Settings and Design: It is an observational cross-sectional type. Materials and Methods: This study was conducted on 90 subjects, including both males and females, divided into three groups: gingivitis (30), Parkinson's disease (PD) (30), and healthy (30). Clinical parameters assessed were gingival bleeding index, Russell's periodontal index (PI), probing pocket depth, and clinical attachment level. Serum and salivary IL-9 levels were weighed by enzyme-linked immunosorbent assay. Statistical Analysis Used: The Statistical Package for the Social Sciences version 22, (IBM, Chicago, IL, USA) was used for evaluation. The normality of the data was checked using the Shapiro-Wilks test. Analysis of variance test was used to compare the means of two or more independent (unrelated) groups, followed by Tukey's post hoc analysis for pair-wise comparison. The analogy between IL-9 and clinical parameters was evaluated using Pearson's correlation coefficient. The probability value was set at 0.05. Results: Statistically significant elevation of saliva and serum IL-9 levels occurred in subjects with gingivitis, followed by PD and health. Conclusions: This study concluded that IL-9 may be indicated as a biomarker in the early stages of periodontal diseases.